2004
DOI: 10.1074/jbc.m405674200
|View full text |Cite
|
Sign up to set email alerts
|

ERK1/2 Controls Na,K-ATPase Activity and Transepithelial Sodium Transport in the Principal Cell of the Cortical Collecting Duct of the Mouse Kidney

Abstract: The collecting duct of normal kidney exhibits significant activity of the MEK1/2-ERK1/2 pathway as shown in vivo by immunostaining of phosphorylated active ERK1/2 (pERK1/2). The MEK1/2-ERK1/2 pathway controls many different ion transports both in proximal and distal nephron, raising the question of whether this pathway is involved in the basal and/or hormone-dependent transepithelial sodium reabsorption in the principal cell of the cortical collecting duct (CCD), a process mediated by the apical epithelial sod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(33 citation statements)
references
References 36 publications
2
31
0
Order By: Relevance
“…35 Another study found no effect of vasopressin on ERK 1/2 phosphorylation in mouse cortical collecting ducts. 36 In contrast, we found that forskolin stimulates ERK 1/2 phosphorylation, similar to the studies in lung cells, rat CCDs, and mpkCCD c14 cells cited above. 24,28,33 We also found that a MEK 1/2 inhibitor reduced Epac-stimulation of UT-A1 phosphorylation.…”
Section: Basic Research Wwwjasnorgsupporting
confidence: 90%
“…35 Another study found no effect of vasopressin on ERK 1/2 phosphorylation in mouse cortical collecting ducts. 36 In contrast, we found that forskolin stimulates ERK 1/2 phosphorylation, similar to the studies in lung cells, rat CCDs, and mpkCCD c14 cells cited above. 24,28,33 We also found that a MEK 1/2 inhibitor reduced Epac-stimulation of UT-A1 phosphorylation.…”
Section: Basic Research Wwwjasnorgsupporting
confidence: 90%
“…Recently, it has been reported that the collecting duct of normal kidney exhibits a significant basal activity of ERK that was not changed by aldosterone or vasopressin. It was concluded that in the principal cell the basal activity of ERK plays a permissive role for Na,K-ATPase function (59). In contrast, there was no clear evidence for a role of ERK activity in ENaC regulation in principal cells under normal conditions, which is consistent with our observation in the oocyte system.…”
Section: Discussionsupporting
confidence: 87%
“…Microdissection was performed in ice-cold DMEM/F-12 (1:1) as described. 20 The following structures were isolated: glomeruli, convoluted and straight proximal tubules, medullary and cortical portions of the thick ascending limb, distal convoluted and connecting tubules, and cortical portions of the collecting ducts. RNA was isolated from microdissected tubules using an RNeasy micro Kit (Qiagen), following the manufacturer's instructions.…”
Section: Surface Biotinylation and Immunoblottingmentioning
confidence: 99%